Comparison of gait recovery patterns according to the paralyzed side in stroke patients: An observational study based on a retrospective chart review (STROBE compliant). Issue 16 (23rd April 2021) - Kim, Cheol-Hyun; Chu, Hongmin; Kang, Geon-Hui; Kim, Kwang-Ho; Lee, Young-Ung; Lim, Hyeon-Seo; Sung, Kang-Keyng; Lee, Sangkwan
Abstract : Abstract: Gait rehabilitations have been abundantly performed for post-stroke patients, because gait is the most important factor for the return of post-stroke patients to daily life. However, conventional uniform gait rehabilitations tend to be tedious and reduce motivation. The aim of this study was to contribute to the development of personalized rehabilitation of gait by identifying differences in gait recovery pattern according to the paralyzed side of post-stroke patients. The gait analysis was performed on stroke patients who are right-handed and can walk independently. We retrospectively analyzed the results of pelvic movements and displacement of center of pressure (COP) during gait using corresponding equipments. To show the difference of gait recovery pattern according to the paralyzed side, we divided subjects into two groups, right (n = 19) and left (n = 20) hemiparesis group. The measured variables were as follows: tilt, obliquity, and rotation symmetries of pelvis; area, velocity, and lateral symmetry of COP. First, in the left hemiparesis group, obliquity ( P  < .01) and rotation ( P  < .01) symmetries of the movement of the pelvis were significantly improved in the follow-up compared to the initial gait analysis. In the right hemiparesis group, tilt ( P  < .001), obliquity ( P  < .001), and rotation ( P  < .05) symmetries were significantly improved in the follow-up compared to the initial gait analysis. Second, COP area and COP velocity values in the follow-up were significantly smaller than those in the initial gait analysis in the left ( P  < .001, P  < .05) and right ( P  < .001, P  < .01) hemiparesis groups. The positive value of lateral symmetry increased, although not a significant difference statistically, as walking ability improved in both groups. In the correlation analysis among variables obtained using Treadmill, there were significant positive linear relationships between the lateral symmetry and the COP area ( P  < .05), and between the COP velocity and the lateral symmetry ( P  < .001) of the follow-up gait analysis in the right hemiparesis group. It was confirmed that the gait recovery pattern differs according to the paralyzed side of post-stroke patients and the role of the intact side, such as moving the COP to the intact side, is important for the improvement of gait function in both groups. This study was registered with the Clinical Research Information Service (CRIS) of the Korea National Institute of Health (NIH), Republic of Korea (KCT0002984) and was approved by the Institutional Review Board (IRB) of the WKUGH (WKIRB [2018-25], November 28, 2018).